ORIGINAL PAPERThe effect of hormone replacement therapy on the left ventricle systolic and diastolic function in postmenopausal women with coronary artery disease - Bręborowicz, Piotr; Mularek-Kubzdela, Tatiana; Oko-Sarnowska, Zofia; Trojnarska, Olga; Maciejewska, Marzena; Bręborowicz, Elżbieta; Warenik-Szymankiewicz, Alina; Cieśliński, Andrzej (Archives of Medical Science, 2005)
Introduction: The aim of this study was to evaluate the effect of hormone replacement therapy (HRT) on the left ventricle systolic and diastolic function. Materials and methods: Fifty-six postmenopausal women with proven coronary artery disease (CAD) were enrolled into the study (31 were assigned to HRT and 25 were matched as a control group). Clinically both groups were comparable. All patients had standard 2D and Doppler echocardiography study at the baseline and after 12 months of follow up. Results: The heart geometry and wall thickness did not change significantly in both groups and were comparable after 12-months of follow-up: EDD: 45.6±6.0 to 44.6±8.1 vs. 47.8±7.1 to 47.2±4.4; ESD: 29.5±7.1 to 29±8.8 vs. 34.3±6.7 to 34.4±7.7; RV: 21.9±6.1 to 23.1±7 vs. 21.5±5.8 to 21.8±3.2; LA: 32±4.7 to 35.6±7.9 vs. 34.3±4.2 to 34±4.4; Ao: 28.8±3.3 to 29.2±4.5 vs. 28.8±2.2 to 28.5±3.4; IVS: 9.9±1.4 to 10±1 vs. 10±1.3 to 10.3±1.6; PW: 10.2±1.1 to 10±1 vs. 10.1±1.6 to 10.3±1.4. Left ventricle systolic and diastolic parameters did not change significantly in both groups and were comparable after 12-months of follow-up: LVEF (%): 64.3±13.4 to 68.4±14.9 vs. 56.6±12.5 to 59.9±13; ESV (ml): 35.3±39.8 to 40.4±57.2 vs. 42.9±23.9 to 38.6±16.4; IVRT (ms): 120.9±22.8 to 112.2±15.4 to 112.8±27.7 to 109.3±12.8; E: A: 1.17±1.17 to 1±0.48 vs. 0.97±0.41 to 0.94±0.35; DCT (E) (ms): 152.4±70.6 to 150.2±50.9 vs. 149.3±69.1 to 176.8±61.4; EDV (ml): 84.9±62.6 to 98.3±69.7 vs. 96.9±43.6 to 96.1±26.9. Conclusions: Short term transdermal HRT has no effect on the left ventricle systolic and diastolic function in women with CAD.